Towards Economic Stagnation? Hungarian Fiscal Policy under the Governments of V. Orbán (1998-2002, 2010-2014) - Guzikowski , Mateusz; Ambroży , Aleksandra (Studia Oeconomica Posnaniensia, 2014)
This article presents a critical analysis of the fiscal reforms introduced by two cabinets led by Viktor Orbán in Hungary (1998-2002 and 2010-2014) as well as recommendations for Poland formulated on the basis of the analysis. Despite the high debt to GDP ratio, the main tool of taking the Hungarian economy out of the economic crisis was an expansion of public spending. It is worth noting that there was also a fiscal austerity package implemented at the same time, which reduced government spending and increased government revenue. Therefore, the uniqueness of the so-called "Hungarian approach" is characterised by a combination of demand policy tools (i.e. an increase in public spending) and austerity package tools (i.e. a rise in public revenue and a fall in public expenditure). The unorthodoxy of the "Hungarian approach" to fiscal consolidation is reflected in an improper ratio of austerity measures (aimed at raising revenues and reducing spending) to demand measures (raising spending). This approach, considered in terms of long-term macroeconomic effects, is open to doubt.